1988
DOI: 10.2527/jas1988.66112791x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Racing Performance in the American Quarter Horse: I. Description of the Data

Abstract: Weighted means of heritability and repeatability estimates from the prior method by age and data source Weighted means of heritability and repeatability estimates from the prior method by distance Number of racing records by year and distance from 1971-1986 Means for racing time by year and distance from 1971-1986 Summary of racing time by month and distance Frequency distributions for number of horses per race by distance Summary of racing times at the five largest tracks for each of five racing distances Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
5
5
1
Order By: Relevance
“…In contrast to Buttram et al (1988), who reported an increase in the superiority of males with increasing racing distance, in the present study no tendency towards increasing or decreasing differences between sexes according to distance was observed. Differences in racing time between sexes normally reflect different physiological characteristics of males and females while racing (Jelinek 1988).…”
Section: Fixed Effectscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to Buttram et al (1988), who reported an increase in the superiority of males with increasing racing distance, in the present study no tendency towards increasing or decreasing differences between sexes according to distance was observed. Differences in racing time between sexes normally reflect different physiological characteristics of males and females while racing (Jelinek 1988).…”
Section: Fixed Effectscontrasting
confidence: 99%
“…Males were significantly superior to females at all distances. This superiority in traits related to racing time has also been reported for trotters (Ojala & Hellman 1987;Saastamoinen & Ojala 1991), Quarter horses (Buttram et al 1988;Villela et al 2002) and Thoroughbreds (Mota et al 1998). The contrast mean at all distances (0.30 s) corresponded to a difference of 1.5 body length between sexes.…”
Section: Fixed Effectssupporting
confidence: 74%
“…The same results were reported by other authors in Thoroughbreds Williamson and Beilharz, 1998;Mota et al, 2005;Sobczynska, 2006;Ekiz and Kocak, 2007) and Quarter horse (Buttram et al, 1988a).…”
Section: Heritability and Repeatabilitysupporting
confidence: 93%
“…In some cases, the percentage of victories has increased and this result was found to be identical to the report of Bugislaus et al (2004). Buttram et al (1988a) has reported that the finished time may be influenced when the CW becomes 56.2 kg, and the average CW was approximately 55 kg in Quarter Horse. However, considering the Quarter Horse race that the racing distance is 320 m, the result was different from that of thoroughbred flat race.…”
Section: Resultssupporting
confidence: 75%
“…According to Tolley et al (1983) and Buttram et al (1988a), although the prize money and the order of finish are important selection traits in racehorses, they are not normally distributed; so, they argued that the records of racehorse without winning prize money, must be eliminated from the data. Also neither the prize money nor the order of finish can be used to examine effect of ratio CW/BW because they do not properly account for the environmental differences affecting the racing performance.…”
Section: Resultsmentioning
confidence: 99%